The use of Microcodium to identify a paraconformity: An example from the Paleogene sequence of Malatya Basin (eastern Turkey) - Kaygili, Sibel; Aksoy, Ercan; Jones, Brian; Acar, Sukru (Elsevier Science Bv, 2019)
The Eocene-Oligocene boundary in eastern Turkey has generally been considered conformable with no break in sedimentation. To the west of Malatya in eastern Turkey, however, the Eocene-Oligocene boundary is located between the Asartepe Member of the Darende Formation (Eocene) and the overlying Murath Formation (Rupellian-early Chattian). Analysis of the strata below the boundary shows that fossil evidence of the Priabonian stage is missing and that the sediments just below the boundary contain numerous Microcodium. Although the precise origin of Microcodium is open to debate, it is generally agreed that they formed as a result of calcification of roots of terrestrial plants. The morphologically diverse array of Microcodium (types (1), (2), and (3); that are up to 1660 mu m in diameter) found in the Asartepe Member, provides clear evidence that terrestrial plants were established before the sediments in the overlying Murath Formation were deposited. This study demonstrates that the presence of Microcodium can highlight the presence of a paraconformity in an otherwise conformable succession of shallow-water sediments. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Malatya Basin; Microcodium; Benthic foraminifera; Paraconformity